Remarks on the Moldovian Campaign of Mikołaj Kamieniecki in 1509 - Gryglewski, Krzysztof; Kuliś, Jakub; Pisarski, Jakub; Cyprian, Cyprian; Agnieszka Gralak (Vade Nobiscum, tom XXII/2021: Studia z wieków dawnych, 2021)
Nicolas Kamienieckis campaign in Moldavia is poorly known and few historians were interested in it. The purpose of this article is to analyse available historical sources about this campaign. Mainly areas of interest are duration of campaign, the way of polish troops in Moldavia and political background of this events. Available historical sources enable to reveal new facts and propose new conclusions about polish campaign in 1509.